Recursos digitales en la asignatura de Ciencias Naturales - Ramos Singaucho, Damaris Yuliana (2023)
Now, educative process and constantly evolution of technology requires that education must be related to digital applications, because they allow an interactive learning between teacher and student. In this way, teacher must assume the responsibility to implement innovative resources, strategies and activities at teaching and learning process. However, today teachers choose to use school textbook as their only one didactic resource, which leads to the so-called textcentrism, that is, the absence of activities and tasks on teaching and learning process, which results in a class improvisation. The objective of the project was to apply the audiovisual resource made in the Powtoon tool for the strengthening of the didactic pedagogical process in the subject of Natural Sciences in the Educational Unit "Dr. José María Velasco Ibarra". The method applied was the inductive theoretical and empirical through the observation technique with its observation guide instrument, which allowed interpreting, explaining and exploring relevant aspects about the digital didactic resources for the teaching and learning of Natural Sciences. The result of the proposal is the application of a video-lesson through a demonstration class, in order to promote autonomous learning through the use of technological tools to strengthen the training process in the subject of Natural Sciences. Therefore, this research project contributes to the innovation processes in the classroom through the incorporation of technology.